Buzzing with possibilities: Training and olfactory generalization in conservation detection dogs for an endangered stonefly species. Issue 4 (21st January 2021) - Rutter, Nicholas J.; Mynott, Julia H.; Howell, Tiffani J.; Stukas, Arthur A.; Pascoe, Jack H.; Bennett, Pauleen C.; Murphy, Nicholas P.
Abstract: Professionally trained conservation detection dogs (CDDs) are taught to locate biological targets, including cryptic and low‐density plant and animal species, but have been largely underused in detecting endangered invertebrates. This pilot study assessed the ability of four volunteer CDD/handler teams to detect the endangered Alpine stonefly (Eustheniidae: Thaumatoperla alpina ). Once trained, all teams identified 100% of the targets when present in container line‐up searches, with no false alerts. In the field, all available dog–handler teams ( n = 3) alerted to the presence of numerous T. alpina individuals, including individuals that were not seen by experienced visual surveyors. Three of the four CDDs also spontaneously alerted (i.e. exhibited olfactory generalization) to a closely related species, the Stirling stonefly ( Thaumatoperla flaveola ), in an initial container search. These preliminary results demonstrate that volunteer dog–handler teams can be trained to detect T. alpina in situ. In addition, CDDs may be able to perform olfactory generalization effectively: from detecting a commonly occurring species to detecting a closely related, rare, or cryptic species.